2015
DOI: 10.1002/aelm.201500069
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Resistance Switching Polarities of Epitaxial BaTiO3 Films by Mediation of Ferroelectricity and Oxygen Vacancies

Abstract: In this work, the observations of different resistive switching polarities of epitaxial BaTiO3 (BTO) thin films fabricated by pulsed laser deposition are reported. The BTO films with various ferroelectric states and oxygen vacancy (VO) concentrations are achieved by carefully controlling the oxygen pressure during the depositions. For films with no ferroelectricity and high VO concentrations, the resistance will change from a low resistance state (LRS) to a high resistance state (HRS) during a positive voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…Therefore, this indicates that the ferroelectric state is preserved in BTO even when charge/ion movement occurs in the second switching process. This is consistent with previous experimental reports and calculations that ferroelectricity is robust in the presence of defects. In contrast, the Pt/STO/NSTO behaves differently in the G – V curve as shown in Figure d, which shows a symmetrical G – V behavior around V = 0 in the low voltage regime (−0.1 V < V < 0.1 V).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, this indicates that the ferroelectric state is preserved in BTO even when charge/ion movement occurs in the second switching process. This is consistent with previous experimental reports and calculations that ferroelectricity is robust in the presence of defects. In contrast, the Pt/STO/NSTO behaves differently in the G – V curve as shown in Figure d, which shows a symmetrical G – V behavior around V = 0 in the low voltage regime (−0.1 V < V < 0.1 V).…”
supporting
confidence: 94%
“…Polarization driven OVM across BTO/LSMO interface was found to be critical in resistive switching in Au/BTO (2.8 nm)/LSMO . Li et al demonstrated that unipolar RS can be switched to bipolar RS in Au/BTO (300 nm)/LSMO device by changing the relative dominance of oxygen vacancy and ferroelectricity in BTO layer. More recently, Hu et al pointed out that oxygen vacancies drifting under intense electric field induces the asymmetry of RV loops and enhances the TER ratio in Sm doped BiFeO 3 FTJ devices.…”
mentioning
confidence: 99%
“…In ferroelectric tunnel junctions, electric‐field biasing allows modifying the polarization state of the ferroelectric, giving rise to distinguishable resistance states of the tunnel barrier, not only useful for memory applications but also for logic operations . It was reported that not only purely electronic mechanism (polarization reversal) but also ionic motions can contribute to the RS states of ferroelectric tunnel junctions . Anyhow, if ferroelectric memory elements are used in crossbar geometry, current sneak and leakage bottlenecks persist.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, higher oxygen pressure in the film deposition process leads to a lower oxygen vacancy concentration and better ferroelectricity in the ferroelectric films. For example, BaTiO 3 (BTO) films with various oxygen vacancy concentrations on the (La,Sr)MnO 3 (LSMO) electrode can be obtained by carefully controlling the deposition oxygen pressure . When the oxygen vacancy concentration is high, the BTO films show weak ferroelectricity, and the BTO/LSMO heterostructures show that the cycle of resistive switching from the LRS to the HRS is clockwise.…”
Section: Approaches To Improve Rs Propertiesmentioning
confidence: 99%